PHYSICAL-MECHANICAL CHARACTERIZATION OF Eucalyptus urophylla WOOD - Lahr, Francisco A. R.; Nogueira, Marta C. de J. A.; Araujo, Victor A. de; Vasconcelos, Juliano S. [UNESP]; Christoforo, Andre L. (Soc Brasil Engenharia Agricola, 2017)
Eucalyptus urophylla consists in a wood-producing species, which offers a natural multiple raw material of good quality for applications in rural and civil constructions. However, Eucalyptus urophylla still has a small utilization as building parts and elements, resulting from the possible ignorance and low diffusion of its structural possibilities. Thereby, the present research aims to measure the main thirteen mechanical properties of Eucalyptus urophylla wood for two different moisture contents, 12% and 30% (green wood). Furthermore, in these two conditions of moisture content evaluation, volumetric mass densities were also evaluated. At the end of this evaluation, which included 2688 determinations, all the obtained results were statistically treated with t-test at a 5% of significance level in order to evaluate the influence of moisture content in the evaluated properties. Twelve mechanical properties were significantly affected by moisture content, and the behavior pattern consisted in increasing the values of the properties with the reduction of the moisture content.
Keywords: Timor White Gum; strength modulus; cracking; shear stress; hardness; density